Parametric Study of the Seismic Response of Base Isolated Liquid Storage Tanks with Lead-Core Elastomeric Bearings - YAZICI, GÖKHAN (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2014)
Field reports from past earthquakes indicate that liquid storage tanks are quite susceptible to earthquake related damages due to the sloshing motion of the contained liquid and that the failure of these structures can have catastrophic impacts on the environment in addition to significant financial losses. Recently, the use of seismic response modification strategies such as base isolation and energy dissipation systems have been extended to liquid storage tanks, particularly large liquified natural gas tanks, in order to protect them from the damaging effects of earthquakes. Base isolation involves the installation of horizontally flexible base isolation bearings under the liquid storage tanks to extend the vibration period of the structure and to provide an additional mechanism for energy dissipation. This paper investigates the effects of the variation of mechanical properties of lead-core elastomeric base isolation bearings on the dynamic response of liquid storage tanks through a comprehensive parametric study which was conducted with a script that uses the Mat lab state-space solvers. The paper begins by outlining the mechanical analogue system to be used for calculating the overturning moment and the base shear in tank wall as well as the free surface displacements for a cylindrical liquid storage tank subjected to horizontal base excitation. The nonlinear force-displacement characteristics of the bearings are modelled with the Bouc-Wen hysteresis model. Results of the parametric study show that base isolation can be effective at decreasing the base shear and that special attention must be paid to the increases in the sloshing displacements in determining the freeboard height.
Keywords: Industrial Facilities; Hysteretic Systems; Random Vibration; Earthquake; Damage